1978
DOI: 10.1111/j.1745-4514.1978.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Effects on Cell Rupture in Plant Protein Recovery

Abstract: Investigation of the effects of selected enzymatic pretreatments of alfalfa leaves on plant protein recovery by mechanical expression of cell contents showed significantly higher crude protein recoveries for enzymatically treated extracts as compared with untreated samples. Protein recovery increases were seen for leaves pretreated with a buffered cellulase and a cellulase‐pectinase mixture. However, protein recoveries were not increased by pretreatment with a pectinase or a phospholipase. The increases were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
8
1
Order By: Relevance
“…32%). These low protein yields were attributed to the pH used for extraction (pH 4-5), which coincided with the minimum solubilities of glycinin and β-conglycinin (1), and confirmed the results obtained in previous studies (2,5). Our results revealed that pH adjustment to a value of high protein solubility (pH 7), followed by stirring for 30 min, was insufficient to totally resolubilize the precipitated proteins.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…32%). These low protein yields were attributed to the pH used for extraction (pH 4-5), which coincided with the minimum solubilities of glycinin and β-conglycinin (1), and confirmed the results obtained in previous studies (2,5). Our results revealed that pH adjustment to a value of high protein solubility (pH 7), followed by stirring for 30 min, was insufficient to totally resolubilize the precipitated proteins.…”
Section: Resultssupporting
confidence: 90%
“…The consecutive addition of 5% IndiAge Super L to a slurry first extracted with 10% Multifect pectinase for 3 h at pH 4 did not enhance the protein extraction compared with extraction without IndiAge Super L. The protein extraction yield and reducing sugar production were the same as those achieved with Multifect pectinase alone (results not shown). The synergistic effect of the cellulase-pectinase mixture on protein extraction obtained with alfalfa leaves was not observed in our experimental conditions with soybeans (5). Even if some of the enzyme cocktails increased the reducing sugar yield, none of them significantly increased protein extraction compared with single enzymes.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Enzymatic methods may be used to increase the yield at neutral pH by liberating more protein from the polysaccharide matrix. Methods describing the application of enzymes, particularly carbohydrases, to improve the extractability of protein from plant sources have been presented (Ghose and Haldar 1969 ;Mudgett et al 1978 ;Grossman et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…[17] This allows rupturing of the plant cells. In addition, use of solvent, which is either produced in-situ (like ethanol and vinegar)[2728] or added separately allows compounds to diffuse from cells into the medium.…”
Section: Methodsmentioning
confidence: 99%